Evolution of complex RNA polymerases: the complete archaeal RNA polymerase structure. - Korkhin, Y; Unligil, U; Littlefield, O; Nelson, P; Stuart, D; Sigler, P; Bell, S; Abrescia, N (2009)
The archaeal RNA polymerase (RNAP) shares structural similarities with eukaryotic RNAP II but requires a reduced subset of general transcription factors for promoter-dependent initiation. To deepen our knowledge of cellular transcription, we have determined the structure of the 13-subunit DNA-directed RNAP from Sulfolobus shibatae at 3.35 Å resolution. The structure contains the full complement of subunits, including RpoG/Rpb8 and the equivalent of the clamp-head and jaw domains of the eukaryotic Rpb1. Furthermore, we have identified subunit Rpo13, an RNAP component in the order Sulfolobales, which contains a helix-turn-helix motif that interacts with the RpoH/Rpb5 and RpoA'/Rpb1 subunits. Its location and topology suggest a role in the formation of the transcription bubble.